0763 Couples-based treatment for OSA: Qualitative analysis of patient, bedpartner and provider perspectives. (25th May 2022) - Troxel, Wendy; DeVettori, Giulia; Kharidia, Shilpi; Gallaway, Saydra; Watt, Melissa; Sundar, Krishna; Gilles, Allyson; Baron, Kelly
Abstract: Introduction: Obstructive sleep apnea (OSA) and its treatment (positive airway pressure; PAP) impacts both patient and bedpartner health and their respective quality of life. Despite the effectiveness of PAP at treating OSA and evidence that PAP adherence benefits both patient and partner, over half of OSA patients are not adherent. Thus, non-adherence to OSA treatment is a couple-level problem, with significant health impacts for both parties. However, bedpartners are rarely integrated into OSA treatments. The current study presents a qualitative analysis of patients, bedpartners, and provider perspectives to inform a novel, couples-based intervention to promote adherence to PAP and sleep health for the couple. Methods: We conducted 3 focus group discussions with patients and their partners, and 3 focus group discussions with sleep medicine providers. Focus groups utilized a standardized interview guide to examine: 1) impact of OSA and PAP treatment on the couple, 2) interdependence of sleep and 3) feasibility of a couples-based sleep health and PAP adherence intervention. Transcripts were transcribed and analyzed using thematic analysis using Dedoose. A thematic analysis process coded for emerging themes across a deductive framework. Results: Participants included 7 heterosexual couples, 2 patients who participated without their partners and 9 sleep medicine providers (1 nurse practitioner, 3 PSG techs and 5 sleep medicine physicians). Results demonstrated awareness of how sleep impacts patient and partner mood, next day functioning, and relationship quality. Patients and partners reported working together using a variety of strategies to overcome challenges to OSA treatment. Couple-level barriers to treatment were discussed, including sleep disruptions from PAP and the impacts of treatment on intimacy. Providers reported the utility of involving partners in the sleep evaluation and during equipment set up. Couples-based treatment was viewed as helpful for facilitating adjustment and adherence to PAP, particularly to help patients trouble-shoot common challenges, such as adjusting to the mask. However, providers expressed some concerns about couples-based treatment among couples with poor relationship quality. Conclusion: Results demonstrate the impact of OSA on the couple and awareness of the importance of including partners in the adjustment to PAP treatment. Findings will be discussed in the context of developing novel behavioral interventions for older adults who face a variety of sleep health issues, in addition to sleep apnea, and in recognition of the dyadic nature of sleep for most adults. Support (If Any): 1 R21 AG067183-01A1